A modeling tool for household biogas burner flame port design - Decker, Thomas J., author; Bradley, Thomas, advisor; Prapas, Jason, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2017)
Anaerobic digestion is a well-known and potentially beneficial process for rural communities in emerging markets, providing the opportunity to generate usable gaseous fuel from agricultural waste. With recent developments in low-cost digestion technology, communities across the world are gaining affordable access to the benefits of anaerobic digestion derived biogas. For example, biogas can displace conventional cooking fuels such as biomass (wood, charcoal, dung) and Liquefied Petroleum Gas (LPG), effectively reducing harmful emissions and fuel cost respectively. To support the ongoing scaling effort of biogas in rural communities, this study has developed and tested a design tool aimed at optimizing flame port geometry for household biogas-fired burners. The tool consists of a multi-component simulation that incorporates three-dimensional CAD designs with simulated chemical kinetics and computational fluid dynamics. An array of circular and rectangular port designs was developed for a widely available biogas stove (called the Lotus) as part of this study. These port designs were created through guidance from previous studies found in the literature. The three highest performing designs identified by the tool were manufactured and tested experimentally to validate tool output and to compare against the original port geometry. The experimental results aligned with the tool's prediction for the three chosen designs. Each design demonstrated improved thermal efficiency relative to the original, with one configuration of circular ports exhibiting superior performance. The results of the study indicated that designing for a targeted range of port hydraulic diameter, velocity and mixture density in the tool is a relevant way to improve the thermal efficiency of a biogas burner. Conversely, the emissions predictions made by the tool were found to be unreliable and incongruent with laboratory experiments.
Keywords: combustion; design; flame port; cookstoves; biogas; emerging markets